O ecoturismo sob a égide da sociedade do consumo: um estudo das Unidades de Conservação de uso sustentável do RN - Soares, Artemisia dos Santos (2011)
Ecotourism, in face to environmental demands and discussions, has achieved prominence in the tourism market and wide global development, occasioning a concern about the need for a scientific deepening through a critical approach of the dynamics of consumption and conservation that permeate this practice. This study addresses the ecotourism under aegis of consumer society, in which is perceived that it constitutes a contester practice of society in which it is embedded, nevertheless has been subjected to the logic of capital through commodification of nature. In order to comprehend the reality presented, this study had as geographical cutting two Conservation Units of Sustainable Use in Rio Grande do Norte state: the Jenipabu Environmental Protection Area (APAJ) and Ponta do Tubarão State Sustainable Development Reserve (RDSEPT). The research sought to investigate the relationship between conservation and consumption and their influences on ecotourism held in the Conservation Units (UCs) of sustainable use selected for this study. To this aim it was made a critical reflection about the relationship conservation versus consumption constant in the practice of ecotourism in UCs in the context of current society, analyzing the historical process of formation of UCs of sustainable use in RN state under the light of the contradictory pair conservation-consumption, as well as looking to apprehend the perception of ecotourism of the actors involved with this practice. It was adopted a qualitative approach under a critical perspective based on bibliographical and documentary research and realization of semi-structured interviews with three groups of actors, namely managers/technician, community and ectourists involved with ecotourism in the selected UCs. The analysis was made using two basic units of analysis (consumption and maintenance) and twelve categories. For definition of units of analysis and categories were taken as reference the authors Santos (1987; 1988; 1994; 2001; 2006), Guerreiro Ramos (1989) and A. B. Rodrigues (1996; 2003), which perform critical to society of consumption and describe the key characteristics of the technical-scientific-informational predominant means, and Diegues (1998; 2000), A. B. Rodrigues (2001), Pires (2002) and Neiman and Rabinovici (2010), which discusse historic and scientifically about the emphasis on conservation present in origins and discourse of ecotourism, describing also its founding characteristics. The main results show that the marketing use of the prefix eco has acted as a new dress for what in reality is in fact ancient, ie, the conservation is used as a justification for another new type of consumption. The results also show that despite the coexistence of commercial and symbolic intentions in both UCs, one can observe the predominance consumer society characteristics in the process of creation and the production activities of APAJ, while in RDSEPT we note the predominance of the conservationist characteristics proclaimed by ecotourism. It can be inferred therefore that tourism held in the APAJ can not be called ecotourism, while the practice found in RDSEPT show an alignment with the guidelines of ecotourism